2016
DOI: 10.1007/s11629-015-3490-1
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of rill development and their effects on runoff and sediment yield under different slope gradients

Abstract: Abstract:process in s study was characterist sediment y gradients a rainfall int setting. Res density ha gradient. T distance of negatively suggested enhance ril the fragmen total erosio value with i is probably erosion beg correlation connection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 29 publications
(28 reference statements)
3
13
1
Order By: Relevance
“…The variation tendency of runoff weakened as slope gradient increased, and this weakening was mainly determined by the extent of transfer between rainfall volume and accumulation infiltration volume. Such findings were consistent with the research results of He et al [13]. Soil particle transfer from the slope is a dynamic development influenced by many factors such as runoff characteristics, soil characteristics, and slope characteristics.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The variation tendency of runoff weakened as slope gradient increased, and this weakening was mainly determined by the extent of transfer between rainfall volume and accumulation infiltration volume. Such findings were consistent with the research results of He et al [13]. Soil particle transfer from the slope is a dynamic development influenced by many factors such as runoff characteristics, soil characteristics, and slope characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have reported that the runoff coefficient was a function of slope gradient and rainfall intensity in different slope gradient cases [4,10,12]. The amount of total erosion tends to stabilize with an increase in slope gradients, which implies there is probably a threshold slope gradient at which soil erosion begins to shift from strong to weak [13]. Fu et al [14] found that the amount of wash load increased with an increasing slope gradient if the gradient was less than 58%; alternatively, the opposite relationship was observed at steeper slopes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, runoff connectivity increases on a tilled surface during rainfall (Antoine, Javaux, & Bielders, ; Darboux, Gascuel‐Odoux, & Davy, ). He, Sun, Gong, Cai, and Jia () also found that increasing slope gradient could enhance rill headward erosion, vertical erosion, and fragmentation of the slope surface. Furthermore, total erosion tends to approach a stable maximum value with increasing slope gradient, which implies that there is probably a critical slope gradient where soil erosion begins to decline.…”
Section: Discussionmentioning
confidence: 99%
“…Rill erosion is one mechanism of soil loss by water on hillslopes (Govers, Giménez, & Oost, 2007;He, Sun, Gong, Cai, & Jia, 2016;Porto, Walling, & Capra, 2014;Xiao, Liu, Zheng, & Zhang, 2017). Rill erosion greatly affects run-off and soil loss occurring on slope surfaces (Fang, Sun, & Tang, 2015;Govers et al, 2007;Wirtz, Seeger, & Ries, 2012) and involves soil particle detachment, transport, and deposition (Nearing et al, 1997).…”
Section: Introductionmentioning
confidence: 99%